Surface albedo in different land-use and cover types in Amazon forest region - Faria,Thiago de Oliveira (2018)
Abstract Albedo is the portion of energy from the Sun that is reflected by the earth's surface, thus being an important variable that controls climate and energy processes on Earth. Surface albedo is directly related to the characteristics of the Earth’s surface materials, making it a useful parameter to evaluate the effects of original soil cover replacement due to human occupation. This study evaluated the changes in the surface albedo values due to the conversion of vegetation to other land uses and to analyze the applicability of the use of albedo in the spatial delimitation of land-use classes in the transitional region between the Cerrado and Amazon biomes. Surface albedo measurements were obtained from processing of Landsat Thematic Mapper data in the Geographic Information System (GIS), and land-use information were collected using Google Earth high-resolution images. The results show that human activities such as the cultivation of crops and burning have contributed substantially to variations in the surface albedo, and that albedo estimates from Landsat imagery have the potential to help in the recognition and delimitation of features of land use and cover.